Analisis Nilai-Nilai Pendidikan Novel Sekayu Karya Nh. Dini - Lies Andayani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
A Sekayu novel is one of those novels classified into a literary novel. It depicts the childhood memories of his author in his adolescence. The stories given in this novel describe the very things that shape the soul of its author. The study employed a descriptive method of analyzing Sekayu novels through literature studies. The purpose of this study is to describe the extrinsic element they contain. Among those extrinsic elements are the educational value. The value of education that the author USES as a reference to are five values listed in GBHN's national educational purposes: 1) responsibility, 2) self-reliance and confidence, 3) knowledge and skill, 4) creativity, and 5) discipline.